Efficacy of the educational program “For responsible sexuality” on the knowledge of sexuality in adolescents of the fifth year of secondary school of the Adventist Educational Institution Puno, Puno, 2016 - Alarcón Rodriguez, Raquel (2019)
Objective: Was to determine the effectiveness of the educational program “For responsible sexuality” onthe knowledge of sexuality in adolescents of the fifth year of secondary school of the Adventist SchoolPuno- Puno, 2016. Methodology: The study was quantitative, quasi-experimental design, applying aPre and post test. The sample consisted of 51 adolescents aged 14 to 17, distributed in two groupsrandomly: experimental group and control group. A questionnaire on sexuality in adolescents was appliedto measure the level of knowledge. The results of the “control group”: in the pre-test a 48.1% low leveland 44.4% medium level, in the post test a result was shown similar to 48.1% at the low level and48.1% at the medium level. Resulted: In the “experimental group” before the application of the program50.0% presented a medium level and 33.3% a low level, only 16.7% a high level, in the post test theknowledge of adolescents was they increased to 83.3% with a high level and 16.7% a medium level, witha significant difference compared to the control group. Conclusion: that at a level of significance of (sig=, 000), the educational program was effective in improving knowledge about sexuality in adolescents.